Answer:
![\huge\boxed{p(x)=4x^3-20x^2+4x+300}](https://tex.z-dn.net/?f=%5Chuge%5Cboxed%7Bp%28x%29%3D4x%5E3-20x%5E2%2B4x%2B300%7D)
Step-by-step explanation:
![\text{If}\ x=4\pm3i\ \text{and}\ x=-3\ \text{are the zeros of a polynomial, then it has a form:}\\\\p(x)=\bigg(x-(4-3i)\bigg)\bigg(x-(4+3i)\bigg)\bigg(x-(-3)\bigg)\bigg(r(x)\bigg)\\\\p(x)=(x-4+3i)(x-4-3i)(x+3)\bigg(r(x)\bigg)\\\\p(x)=\underbrace{\bigg((x-4)+3i\bigg)\bigg((x-4)-3i\bigg)}_{\text{use}\ (a+b)(a-b)=a^2-b^2}(x+3)\bigg(r(x)\bigg)\\\\p(x)=\bigg((x-4)^2-(3i)^2\bigg)(x+3)\bigg(r(x)\bigg)\qquad\text{use}\ (a-b)^2=a^2-2ab+b^2](https://tex.z-dn.net/?f=%5Ctext%7BIf%7D%5C%20x%3D4%5Cpm3i%5C%20%5Ctext%7Band%7D%5C%20x%3D-3%5C%20%5Ctext%7Bare%20the%20zeros%20of%20a%20polynomial%2C%20then%20it%20has%20%20a%20form%3A%7D%5C%5C%5C%5Cp%28x%29%3D%5Cbigg%28x-%284-3i%29%5Cbigg%29%5Cbigg%28x-%284%2B3i%29%5Cbigg%29%5Cbigg%28x-%28-3%29%5Cbigg%29%5Cbigg%28r%28x%29%5Cbigg%29%5C%5C%5C%5Cp%28x%29%3D%28x-4%2B3i%29%28x-4-3i%29%28x%2B3%29%5Cbigg%28r%28x%29%5Cbigg%29%5C%5C%5C%5Cp%28x%29%3D%5Cunderbrace%7B%5Cbigg%28%28x-4%29%2B3i%5Cbigg%29%5Cbigg%28%28x-4%29-3i%5Cbigg%29%7D_%7B%5Ctext%7Buse%7D%5C%20%28a%2Bb%29%28a-b%29%3Da%5E2-b%5E2%7D%28x%2B3%29%5Cbigg%28r%28x%29%5Cbigg%29%5C%5C%5C%5Cp%28x%29%3D%5Cbigg%28%28x-4%29%5E2-%283i%29%5E2%5Cbigg%29%28x%2B3%29%5Cbigg%28r%28x%29%5Cbigg%29%5Cqquad%5Ctext%7Buse%7D%5C%20%28a-b%29%5E2%3Da%5E2-2ab%2Bb%5E2)
![p(x)=(x^2-2(x)(4)+4^2-3^2i^2)(x+3)\bigg(r(x)\bigg)\qquad\text{use}\ i^2=-1\\\\p(x)=(x^2-8x+16-9(-1))(x+3)\bigg(r(x)\bigg)\\\\p(x)=(x^2-8x+16+9)(x+3)\bigg(r(x)\bigg)\\\\p(x)=(x^2-8x+25)(x+3)\bigg(r(x)\bigg)\qquad\text{use FOIL}:\ (a+b)(c+d)=ac+ad+bc+bd\\\\p(x)=\bigg((x^2)(x)+(x^2)(3)+(-8x)(x)+(-8x)(3)+(25)(x)+(25)(3)\bigg)\bigg(r(x)\bigg)\\\\p(x)=(x^3+3x^2-8x^2-24x+25x+75)\bigg(r(x)\bigg)\qquad\text{combine like terms}\\\\p(x)=(x^3-5x^2+x+75)\bigg(r(x)\bigg)](https://tex.z-dn.net/?f=p%28x%29%3D%28x%5E2-2%28x%29%284%29%2B4%5E2-3%5E2i%5E2%29%28x%2B3%29%5Cbigg%28r%28x%29%5Cbigg%29%5Cqquad%5Ctext%7Buse%7D%5C%20i%5E2%3D-1%5C%5C%5C%5Cp%28x%29%3D%28x%5E2-8x%2B16-9%28-1%29%29%28x%2B3%29%5Cbigg%28r%28x%29%5Cbigg%29%5C%5C%5C%5Cp%28x%29%3D%28x%5E2-8x%2B16%2B9%29%28x%2B3%29%5Cbigg%28r%28x%29%5Cbigg%29%5C%5C%5C%5Cp%28x%29%3D%28x%5E2-8x%2B25%29%28x%2B3%29%5Cbigg%28r%28x%29%5Cbigg%29%5Cqquad%5Ctext%7Buse%20FOIL%7D%3A%5C%20%28a%2Bb%29%28c%2Bd%29%3Dac%2Bad%2Bbc%2Bbd%5C%5C%5C%5Cp%28x%29%3D%5Cbigg%28%28x%5E2%29%28x%29%2B%28x%5E2%29%283%29%2B%28-8x%29%28x%29%2B%28-8x%29%283%29%2B%2825%29%28x%29%2B%2825%29%283%29%5Cbigg%29%5Cbigg%28r%28x%29%5Cbigg%29%5C%5C%5C%5Cp%28x%29%3D%28x%5E3%2B3x%5E2-8x%5E2-24x%2B25x%2B75%29%5Cbigg%28r%28x%29%5Cbigg%29%5Cqquad%5Ctext%7Bcombine%20like%20terms%7D%5C%5C%5C%5Cp%28x%29%3D%28x%5E3-5x%5E2%2Bx%2B75%29%5Cbigg%28r%28x%29%5Cbigg%29)
![\text{The y-intercept is at 300}.\\\\\text{For}\ w(x)=a_nx^n+a_{n-1}x^{n-1}+a_{n-2}x^{n-2}+...+a_1x+a_0\\\\\text{y-intercept is}\ a_0\\\\\text{Therefore for}\ p(x)=(x^3-5x^2+x+75)\bigg(r(x)\bigg)\\\\\text{y-intercet is}\ 75\bigg(r(x)\bigg)\\\\75\bigg(r(x)\bigg)=300\qquad\text{divide both sides by 75}\\\\r(x)=4\\\\\text{Finally:}\\\\p(x)=(x^3-5x^2+x+75)(4)\qquad\text{use the distributive property}\\\\p(x)=(x^3)(4)+(-5x^2)(4)+(x)(4)+(75)(4)\\\\p(x)=4x^3-20x^2+4x+300](https://tex.z-dn.net/?f=%5Ctext%7BThe%20y-intercept%20is%20at%20300%7D.%5C%5C%5C%5C%5Ctext%7BFor%7D%5C%20w%28x%29%3Da_nx%5En%2Ba_%7Bn-1%7Dx%5E%7Bn-1%7D%2Ba_%7Bn-2%7Dx%5E%7Bn-2%7D%2B...%2Ba_1x%2Ba_0%5C%5C%5C%5C%5Ctext%7By-intercept%20is%7D%5C%20a_0%5C%5C%5C%5C%5Ctext%7BTherefore%20for%7D%5C%20p%28x%29%3D%28x%5E3-5x%5E2%2Bx%2B75%29%5Cbigg%28r%28x%29%5Cbigg%29%5C%5C%5C%5C%5Ctext%7By-intercet%20is%7D%5C%2075%5Cbigg%28r%28x%29%5Cbigg%29%5C%5C%5C%5C75%5Cbigg%28r%28x%29%5Cbigg%29%3D300%5Cqquad%5Ctext%7Bdivide%20both%20sides%20by%2075%7D%5C%5C%5C%5Cr%28x%29%3D4%5C%5C%5C%5C%5Ctext%7BFinally%3A%7D%5C%5C%5C%5Cp%28x%29%3D%28x%5E3-5x%5E2%2Bx%2B75%29%284%29%5Cqquad%5Ctext%7Buse%20the%20distributive%20property%7D%5C%5C%5C%5Cp%28x%29%3D%28x%5E3%29%284%29%2B%28-5x%5E2%29%284%29%2B%28x%29%284%29%2B%2875%29%284%29%5C%5C%5C%5Cp%28x%29%3D4x%5E3-20x%5E2%2B4x%2B300)
Answer:
a = 4 + -1.333333333b
Step-by-step explanation:
Simplifying
3a + 4b = 12
Solving
3a + 4b = 12
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '-4b' to each side of the equation.
3a + 4b + -4b = 12 + -4b
Combine like terms: 4b + -4b = 0
3a + 0 = 12 + -4b
3a = 12 + -4b
Divide each side by '3'.
a = 4 + -1.333333333b
Simplifying
a = 4 + -1.333333333b
It's C ray AC because it's the same length just opposite
7m+2=7n−5
Swap sides so that all variable terms are on the left hand side.
7n−5=7m+2
Add 5 to both sides.
7n=7m+2+5
Add 2 and 5 to get 7.
7n=7m+7
Divide both sides by 7.
7
7n
=
7
7m+7
Dividing by 7 undoes the multiplication by 7.
n=
7
7m+7
Divide 7+7m by 7.
n=m+1
Answer:
![\boxed{ \ - \frac{3}{45} }](https://tex.z-dn.net/?f=%20%20%5Cboxed%7B%20%5C%20-%20%20%5Cfrac%7B3%7D%7B45%7D%20%7D)
Step-by-step explanation:
10 3/9 - 10 2/5
we need to convert mixed fractions to improper fractions
![10 \frac{3}{9} = \frac{10 \times 9 + 3}{9} = \frac{93}{9}](https://tex.z-dn.net/?f=10%20%5Cfrac%7B3%7D%7B9%7D%20%20%3D%20%20%5Cfrac%7B10%20%5Ctimes%209%20%2B%203%7D%7B9%7D%20%20%3D%20%20%5Cfrac%7B93%7D%7B9%7D%20)
![10 \frac{2}{5} = \frac{10 \times 5 + 2}{5} = \frac{52}{5}](https://tex.z-dn.net/?f=10%20%5Cfrac%7B2%7D%7B5%7D%20%20%3D%20%20%5Cfrac%7B10%20%5Ctimes%205%20%2B%202%7D%7B5%7D%20%20%3D%20%20%5Cfrac%7B52%7D%7B5%7D%20)
Now, we have 93/9 - 52/5
We need to equate the denominators, before subtracting them.
![\frac{93}{9} - \frac{52}{5} = \frac{93 \times 5}{45} - \frac{52 \times 9}{45}](https://tex.z-dn.net/?f=%20%20%5Cfrac%7B93%7D%7B9%7D%20%20-%20%20%5Cfrac%7B52%7D%7B5%7D%20%20%3D%20%20%5Cfrac%7B93%20%5Ctimes%205%7D%7B45%7D%20%20-%20%20%5Cfrac%7B52%20%5Ctimes%209%7D%7B45%7D%20)
![\frac{465}{45} - \frac{468}{45}](https://tex.z-dn.net/?f=%20%20%5Cfrac%7B465%7D%7B45%7D%20%20-%20%20%5Cfrac%7B468%7D%7B45%7D%20)
![\frac{ - 3}{45}](https://tex.z-dn.net/?f=%20%20%5Cfrac%7B%20-%203%7D%7B45%7D%20)
![\boxed{ - \frac{3}{45} }](https://tex.z-dn.net/?f=%20%20%5Cboxed%7B%20-%20%20%5Cfrac%7B3%7D%7B45%7D%20%7D)
The result of 10 3/9- 10 2/5 is - 3/45